Islamic Perspectives on Climate Justice: Reconstructing Environmental Ethics Through Maqāṣid al-Sharī‘ah - Moh. Imron Rosidi; Ali Anhar Syi’bul Huda; Syalaisha Renaisse Fathiha; Muslim Muslim; Wan Muna Marwah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Climate justice has emerged as a critical normative issue that requires ethical and legal frameworks capable of integrating environmental sustainability with social welfare and intergenerational responsibility. This study aims to reconstruct Islamic environmental ethics through the perspective of maqāṣid al-sharī‘ah and to formulate an integrated conceptual framework for contemporary climate governance. The research employed a qualitative normative legal approach using library research, drawing upon recent scholarly literature on Islamic environmental law, ecological jurisprudence, environmental ethics, and maqāṣid al-sharī‘ah. Data were analyzed through qualitative content analysis and conceptual synthesis to identify key normative principles and develop an Eco-Maqāṣid framework. The findings demonstrate that environmental preservation should be understood as a foundational legal objective supporting the realization of public welfare, justice, and sustainable development. The study further shows that integrating the principles of tawḥīd, khilāfah, mīzān, and maqāṣid al-sharī‘ah provides a coherent ethical foundation for preventive environmental governance, institutional accountability, and climate resilience. The proposed Eco-Maqāṣid framework contributes theoretically by synthesizing fragmented discussions on Islamic environmental ethics into a unified analytical model and offers a normative reference for strengthening climate governance within contemporary Islamic legal thought.